SIMULATION OF LOCOMOTIVE REPAIR ORGANIZATION BY THE METHODS OF QUEUE SYSTEMS THEORY - Bodnar, B. E.; Ochkasov, O. B.; Bodnar, E. B.; Hryshechkina, T. S.; Ocheretnyuk М. V. (Science and Transport Progress, 2018)
Purpose. The article is aimed to evaluate the influence of locomotives` operation and reliability indicators on the system of locomotives repair organization in depot, using the methods of queue theory. Methodology. The article describes the locomotive repair workshop using the terms and concepts of the queue systems theory (QST). The tasks solved during simulation of the repair workshop operation are formulated, the list of initial data and simulation results is given. A graphical simulation environment Simulink was used as a software simulation tool. Findings. It was established that the main indicators of locomotive depot operation are affected by the volume of traffic, the reliability of locomotives, the rule used to select locomotives from the queue, the number of operating repair bays. The developed model of the depot repair workshop will make possible rational planning of the repair workshop`s equipment use, the human capital, the time of putting the locomotives into repair taking into account the workshop loading uniformity, as well as to improve the repair parts supply logistics. This model in a simplified form describes the repair process of the main diesel locomotive fleet, and can be supplemented depending on the repair type performed in the depot. Originality. The paper presents the locomotive repair depot as an object of the queue systems theory. The simulation model of the locomotive repair depot was developed. It allows analyzing the influence of various factors on the system of locomotives` repair organization in the depot. Practical value. The obtained results make it possible to determine the influence of locomotives` operation and reliability indicators on the organization of the locomotive repair depot operation. In further studies, the developed model can be used to improve the system of repair organization on the railway network when introducing new series of locomotives and changing the strategy of their maintenance.